1995
DOI: 10.1183/09031936.95.08081357
|View full text |Cite
|
Sign up to set email alerts
|

Effect of oxidant air pollutants on the respiratory system: insights from experimental animal research

Abstract: In the present paper, we have reviewed experimental animal studies on the effects of the two most important oxidant airborne pollutants, nitrogen dioxide and ozone, on the respiratory system.The toxic effects depend on concentration and length of exposure, and are generally similar for both oxidants, with ozone operative at lower concentrations. High doses of both oxidants cause death due to lung oedema Exposure to sublethal levels causes functional alterations such as airflow limitation and airway hyperrespon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
62
1
6

Year Published

1996
1996
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 167 publications
(276 reference statements)
3
62
1
6
Order By: Relevance
“…Highly reactive-hydroscopic gases (e.g. SO 2 ) are absorbed almost entirely in the nose during normal nasal breathing; on the other hand, ozone (O 3 ) readily can reach the alveoli. Exercise during exposure increases the pollutant effect on ventilatory function.…”
Section: Pollutant Factors Of Importancementioning
confidence: 99%
See 2 more Smart Citations
“…Highly reactive-hydroscopic gases (e.g. SO 2 ) are absorbed almost entirely in the nose during normal nasal breathing; on the other hand, ozone (O 3 ) readily can reach the alveoli. Exercise during exposure increases the pollutant effect on ventilatory function.…”
Section: Pollutant Factors Of Importancementioning
confidence: 99%
“…There has been a study in Los Angeles that showed significant associations both of O 3 and nitrogen dioxide (NO 2 ) with total and cause-specific mortality [42]; PM was not significant. No lowest observed effect levels (LOELs) have been defined for acute mortality associated with O 3 or NO 2 .…”
Section: Mortalitymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies mainly focused on the background air pollution. However, the impact of air pollutants on health is closely related to the extent of individual exposure, which includes not only exposure concentration but also exposure time [14]. Although numerous studies indicated that the airway health could be caused by short-term exposure to air pollutants at high concentration, long-term exposure to air pollutants at low concentrations may also induce an equivalent effect, which suggests an accumulative effect of air pollution exposure on health [15][16][17][18][19].…”
mentioning
confidence: 99%
“…Mücke and Wagner [13] reported that even NO 2 at low concentrations can affect respiratory tract by increasing respiratory resistance, changing pulmonary functions, decreasing defence against disease and causing morphological damage to lungs. Short-term exposures to about 100 parts per billion (ppb) were found to be harmful to rats in an experimental study [14], while long-term effects have been perceived to reduce immunity, leading to respiratory infection [15]. Using NO 2 as an indicator pollutant in this study would help us determine whether the levels of air pollution concentration present in a particular region may cause adverse health impacts, and make recommendations for pollution control, considering that NO 2 emanated from combustion is accompanied by other pollutants.…”
Section: Effects Of Nitrogen Dioxide Exposurementioning
confidence: 99%